ANALISIS KANDUNGAN AIR DAN pH NATA DE COCO SEBAGAI BAHAN BAKU PEMBUATAN PRODUK MINUMAN - Bahar, Imelda; Daulay, Rizky Oktaviani (Politeknik ATI Padang, 2017)
In the nata there are bacteria Acetobacter xylinum from starter, the growth is at pH 3.0 - 6.0. However, the optimum pH growth ranged from 3.0 to 4.5. water content in nata de coco is not more than 20%. One form of processed nata as food produced for soft drinks, which are require processing the requirements, such as not contaminated. The cause of contamination on the product can come from raw materials or during the production process. While the cause of contamination on the product is derived from the raw material of the beverage itself, such as nata de coco where before the ingredients of the beverage water content should be measured and not passed from the standard. Measurement of water content by using initial weighing with which has been filtered while the pH with pH meter. The results of the water content 8% - 19%, for pH values ranged between 3.10 - 3.64 in accordance with the standard quality requirements SNI 01-4317-1996: Water content ≤ 20%, pH 3.00-4.00.